Reversible photoswitching of the DNA-binding properties of styrylquinolizinium derivatives through photochromic [2 + 2] cycloaddition and cycloreversion - Kölsch, Sarah; Ihmels, Heiko; Mattay, Jochen; Sewald, Norbert; Patrick, Brian O. (Beilstein Journal of Organic Chemistry, 2020)
It was demonstrated that styrylquinolizinium derivatives may be applied as photoswitchable DNA ligands. At lower ligand:DNA ratios (≤1.5), these compounds bind to duplex DNA by intercalation, with binding constants ranging from Kb = 4.1 × 104 M to 2.6 × 105 M (four examples), as shown by photometric and fluorimetric titrations as well as by CD and LD spectroscopic analyses. Upon irradiation at 450 nm, the methoxy-substituted styrylquinolizinium derivatives form the corresponding syn head-to-tail cyclobutanes in a selective [2 + 2] photocycloaddition, as revealed by X-ray diffraction analysis of the reaction products. These photodimers bind to DNA only weakly by outside-edge association, but they release the intercalating monomers upon irradiation at 315 nm in the presence of DNA. As a result, it is possible to switch between these two ligands and likewise between two different binding modes by irradiation with different excitation wavelengths.
Keywords: azoniahetarenes; DNA ligands; photodimerization; photoswitches

(untitled) - Rahman, A.; O'Sullivan, P.; Rozas, I. (Med. Chem. Commun., 2019)

(untitled) - Bhaduri, S.; Ranjan, N.; Arya, D. P. (Beilstein J. Org. Chem., 2018)

(untitled) - Wang, M.; Yu, Y.; Liang, C.; Lu, A.; Zhang, G. (Int. J. Mol. Sci., 2016)

(untitled) - Rescifina, A.; Zagni, C.; Varrica, M. G.; Pistarà, V.; Corsaro, A. (Eur. J. Med. Chem., 2014)

(untitled) - Bolhuis, A.; Aldrich-Wright, J. R. (Bioorg. Chem., 2014)

(untitled) - Banerjee, S.; Veale, E. B.; Phelan, C. M.; Murphy, S. A.; Tocci, G. M.; Gillespie, L. J.; Frimannsson, D. O.; Kelly, J. M.; Gunnlaugsson, T. (Chem. Soc. Rev., 2013)

(untitled) - Pazos, E.; Mosquera, J.; Vázquez, M. E.; Mascareñas, J. L. (ChemBioChem, 2011)

Materials Science of DNA Chemistry - Ihmels, H.; Thomas, L. (Intercalation of Organic Ligands as a Tool to Modify the Properties of DNA, 2011)

(untitled) - Pett, L.; Hartley, J.; Kiakos, K. (Curr. Top. Med. Chem., 2015)

(untitled) - Pommier, Y. (ACS Chem. Biol., 2013)

(untitled) - Carelle, N.; Piotto, E.; Bellanger, A.; Germanaud, J.; Thuillier, A.; Khayat, D. (Cancer, 2002)

(untitled) - Sonis, S. T.; Elting, L. S.; Keefe, D.; Peterson, D. E.; Schubert, M.; Hauer-Jensen, M.; Bekele, B. N.; Raber-Durlacher, J.; Donnelly, J. P.; Rubenstein, E. B. (Cancer, 2004)

(untitled) - Ludwig, H.; Van Belle, S.; Barrett-Lee, P.; Birgegård, G.; Bokemeyer, C.; Gascón, P.; Kosmidis, P.; Krzakowski, M.; Nortier, J.; Olmi, P.; Schneider, M.; Schrijvers, D. (Eur. J. Cancer, 2004)

Green Chemical Reactions - Albini, A.; Fagnoni, M. (The Greenest Reagent in Organic Synthesis: Light, 2008)

(untitled) - Pianowski, Z. L. (Chem. – Eur. J., 2019)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Szymański, W.; Beierle, J. M.; Kistemaker, H. A. V.; Velema, W. A.; Feringa, B. L. (Chem. Rev., 2013)

(untitled) - Velema, W. A.; Szymanski, W.; Feringa, B. L. (J. Am. Chem. Soc., 2014)

(untitled) - Andersson, J.; Li, S.; Lincoln, P.; Andréasson, J. (J. Am. Chem. Soc., 2008)

(untitled) - Hammarson, M.; Nilsson, J. R.; Li, S.; Lincoln, P.; Andréasson, J. (Chem. – Eur. J., 2014)

(untitled) - Brieke, C.; Heckel, A. (Chem. – Eur. J., 2013)

(untitled) - Czerwinska, I.; Juskowiak, B. (Int. J. Biol. Macromol., 2012)

(untitled) - Fortuna, C. G.; Mazzucato, U.; Musumarra, G.; Pannacci, D.; Spalletti, A. (J. Photochem. Photobiol., A, 2010)

(untitled) - Dohno, C.; Uno, S.-n.; Nakatani, K. (J. Am. Chem. Soc., 2007)

(untitled) - Dohno, C.; Yamamoto, T.; Nakatani, K. (Eur. J. Org. Chem., 2009)

(untitled) - Basak, A.; Mitra, D.; Kar, M.; Biradha, K. (Chem. Commun., 2008)

(untitled) - Wang, X.; Huang, J.; Zhou, Y.; Yan, S.; Weng, X.; Wu, X.; Deng, M.; Zhou, X. (Angew. Chem., 2010)

(untitled) - Bergen, A.; Rudiuk, S.; Morel, M.; Le Saux, T.; Ihmels, H.; Baigl, D. (Nano Lett., 2016)

(untitled) - Linares, M.; Sun, H.; Biler, M.; Andréasson, J.; Norman, P. (Phys. Chem. Chem. Phys., 2019)

(untitled) - Mammana, A.; Carroll, G. T.; Areephong, J.; Feringa, B. L. (J. Phys. Chem. B, 2011)

(untitled) - Pace, T. C. S.; Müller, V.; Li, S.; Lincoln, P.; Andréasson, J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Presa, A.; Barrios, L.; Cirera, J.; Korrodi-Gregório, L.; Pérez-Tomás, R.; Teat, S. J.; Gamez, P. (Inorg. Chem., 2016)

(untitled) - Paramonov, S. V.; Lokshin, V.; Ihmels, H.; Fedorova, O. A. (Photochem. Photobiol. Sci., 2011)

(untitled) - Ihmels, H.; Mattay, J.; May, F.; Thomas, L. (Org. Biomol. Chem., 2013)

(untitled) - Juskowiak, B.; Chudak, M. (Photochem. Photobiol., 2004)

(untitled) - Ihmels, H.; Otto, D.; Dall'Acqua, F.; Faccio, A.; Moro, S.; Viola, G. (J. Org. Chem., 2006)

(untitled) - Ramamurthy, V.; Sivaguru, J. (Chem. Rev., 2016)

(untitled) - Bibal, B.; Mongin, C.; Bassani, D. M. (Chem. Soc. Rev., 2014)

(untitled) - MacGillivray, L. R.; Papaefstathiou, G. S.; Friščić, T.; Hamilton, T. D.; Bučar, D.-K.; Chu, Q.; Varshney, D. B.; Georgiev, I. G. (Acc. Chem. Res., 2008)

(untitled) - Nagarathinam, M.; Peedikakkal, A. M. P.; Vittal, J. J. (Chem. Commun., 2008)

(untitled) - Mishra, A.; Behera, R. K.; Behera, P. K.; Mishra, B. K.; Behera, G. B. (Chem. Rev., 2000)

(untitled) - Fedorova, O. A.; Saifutiarova, A. E.; Gulakova, E. N.; Guskova, E. O.; Aliyeu, T. M.; Shepel, N. E.; Fedorov, Y. V. (Photochem. Photobiol. Sci., 2019)

(untitled) - Wei, P.; Zhang, J.-X.; Zhao, Z.; Chen, Y.; He, X.; Chen, M.; Gong, J.; Sung, H. H.-Y.; Williams, I. D.; Lam, J. W. Y.; Tang, B. Z. (J. Am. Chem. Soc., 2018)

(untitled) - Berdnikova, D. V.; Aliyeu, T. M.; Delbaere, S.; Fedorov, Y. V.; Jonusauskas, G.; Novikov, V. V.; Pavlov, A. A.; Peregudov, A. S.; Shepel', N. E.; Zubkov, F. I.; Fedorova, О. A. (Dyes Pigm., 2017)

(untitled) - Budyka, M. F.; Gavrishova, T. N.; Potashova, N. I.; Chernyak, A. V. (Mendeleev Commun., 2015)

(untitled) - Ushakov, E. N.; Vedernikov, A. I.; Lobova, N. A.; Dmitrieva, S. N.; Kuz’mina, L. G.; Moiseeva, A. A.; Howard, J. A. K.; Alfimov, M. V.; Gromov, S. P. (J. Phys. Chem. A, 2015)

(untitled) - Berdnikova, D. V.; Sosnin, N. I.; Fedorova, O. A.; Ihmels, H. (Org. Biomol. Chem., 2018)

(untitled) - Botti, V.; Cesaretti, A.; Ban, Ž.; Crnolatac, I.; Consiglio, G.; Elisei, F.; Piantanida, I. (Org. Biomol. Chem., 2019)

(untitled) - Wang, M.-Q.; Liu, S.; Tang, C.-P.; Raza, A.; Li, S.; Gao, L.-X.; Sun, J.; Guo, S.-P. (Dyes Pigm., 2017)

(untitled) - Narayanaswamy, N.; Narra, S.; Nair, R. R.; Saini, D. K.; Kondaiah, P.; Govindaraju, T. (Chem. Sci., 2016)

(untitled) - Berdnikova, D. V.; Fedorova, O. A.; Tulyakova, E. V.; Li, H.; Kölsch, S.; Ihmels, H. (Photochem. Photobiol., 2015)

(untitled) - Narayanaswamy, N.; Das, S.; Samanta, P. K.; Banu, K.; Sharma, G. P.; Mondal, N.; Dhar, S. K.; Pati, S. K.; Govindaraju, T. (Nucleic Acids Res., 2015)

(untitled) - Xie, X.; Choi, B.; Largy, E.; Guillot, R.; Granzhan, A.; Teulade-Fichou, M.-P. (Chem. – Eur. J., 2013)

(untitled) - Mazzoli, A.; Carlotti, B.; Consiglio, G.; Fortuna, C. G.; Miolo, G.; Spalletti, A. (Photochem. Photobiol. Sci., 2014)

(untitled) - Mazzoli, A.; Carlotti, B.; Bonaccorso, C.; Fortuna, C. G.; Mazzucato, U.; Miolo, G.; Spalletti, A. (Photochem. Photobiol. Sci., 2011)

(untitled) - Fortuna, C. G.; Barresi, V.; Berellini, G.; Musumarra, G. (Bioorg. Med. Chem., 2008)

(untitled) - Fortuna, C. G.; Barresi, V.; Bonaccorso, C.; Consiglio, G.; Failla, S.; Trovato-Salinaro, A.; Musumarra, G. (Eur. J. Med. Chem., 2012)

(untitled) - Barresi, V.; Bonaccorso, C.; Consiglio, G.; Goracci, L.; Musso, N.; Musumarra, G.; Satriano, C.; Fortuna, C. G. (Mol. BioSyst., 2013)

(untitled) - Schmidt, D.; Rodat, T.; Heintze, L.; Weber, J.; Horbert, R.; Girreser, U.; Raeker, T.; Bußmann, L.; Kriegs, M.; Hartke, B.; Peifer, C. (ChemMedChem, 2018)

(untitled) - Granzhan, A.; Ihmels, H. (Synlett, 2016)

(untitled) - Ihmels, H.; Karbasiyoun, M.; Löhl, K.; Stremmel, C. (Org. Biomol. Chem., 2019)

(untitled) - Xie, X.; Zuffo, M.; Teulade-Fichou, M.-P.; Granzhan, A. (Beilstein J. Org. Chem., 2019)

(untitled) - Das, A. K.; Ihmels, H.; Kölsch, S. (Photochem. Photobiol. Sci., 2019)

(untitled) - Chang, L.; Liu, C.; He, S.; Lu, Y.; Zhang, S.; Zhao, L.; Zeng, X. (Sens. Actuators, B, 2014)

(untitled) - Yao, H.; Chang, L.; Liu, C.; Jiao, X.; He, S.; Liu, H.; Zeng, X. (J. Fluoresc., 2015)

(untitled) - Zacharioudakis, E.; Cañeque, T.; Custodio, R.; Müller, S.; Cuadro, A. M.; Vaquero, J. J.; Rodriguez, R. (Bioorg. Med. Chem. Lett., 2017)

(untitled) - Maçoas, E.; Marcelo, G.; Pinto, S.; Cañeque, T.; Cuadro, A. M.; Vaquero, J. J.; Martinho, J. M. G. (Chem. Commun., 2011)

(untitled) - Richards, A.; Stevens, T. S. (J. Chem. Soc., 1958)

(untitled) - Marcelo, G.; Pinto, S.; Cañeque, T.; Mariz, I. F. A.; Cuadro, A. M.; Vaquero, J. J.; Martinho, J. M. G.; Maçôas, E. M. S. (J. Phys. Chem. A, 2015)

(untitled) - Pithan, P. M.; Decker, D.; Druzhinin, S. I.; Ihmels, H.; Schönherr, H.; Voß, Y. (RSC Adv., 2017)

(untitled) - Jones, G.; Jackson, W. R.; Choi, C.-y.; Bergmark, W. R. (J. Phys. Chem., 1985)

(untitled) - Sirajuddin, M.; Ali, S.; Badshah, A. (J. Photochem. Photobiol., B, 2013)

(untitled) - Stootman, F. H.; Fisher, D. M.; Rodger, A.; Aldrich-Wright, J. R. (Analyst, 2006)

(untitled) - Šmidlehner, T.; Piantanida, I.; Pescitelli, G. (Beilstein J. Org. Chem., 2018)

Linear Dichroism and Circular Dichroism - Norden, B.; Rodger, A.; Dafforn, T. (Royal Society of Chemistry, 2010)

(untitled) - Nordén, B.; Kurucsev, T. (J. Mol. Recognit., 1994)

(untitled) - Holzmann, N.; Bernasconi, L.; Callaghan, K. M.; Bisby, R. H.; Parker, A. W. (Chem. Phys. Lett., 2018)

(untitled) - Amjaour, H.; Wang, Z.; Mabin, M.; Puttkammer, J.; Busch, S.; Chu, Q. R. (Chem. Commun., 2019)

(untitled) - Ihmels, H.; Luo, J. (J. Photochem. Photobiol., A, 2008)

(untitled) - Mondal, B.; Zhang, T.; Prabhakar, R.; Captain, B.; Ramamurthy, V. (Photochem. Photobiol. Sci., 2014)

(untitled) - Yamada, S.; Azuma, Y.; Aya, K. (Tetrahedron Lett., 2014)

(untitled) - Mondal, B.; Captain, B.; Ramamurthy, V. (Photochem. Photobiol. Sci., 2011)

(untitled) - Hill, Y.; Linares, M.; Briceño, A. (New J. Chem., 2012)

(untitled) - Kole, G. K.; Tan, G. K.; Vittal, J. J. (J. Org. Chem., 2011)

(untitled) - Peedikakkal, A. M. P.; Peh, C. S. Y.; Koh, L. L.; Vittal, J. J. (Inorg. Chem., 2010)

(untitled) - Horner, M.; Hünig, S. (Liebigs Ann. Chem., 1982)